Terrae Motus. - Villa Campolieto Ercolano; Fondazione Amelio - Instituto per l'Arte Contemporanea, Napoli (Napoli : Electa, 1984)
Alfano, Carlo ; Anzinger, Siegfried ; Barcelò, Miquel ; Beuys, Joseph ; Brown, James ; Cragg, Tony ; Cutrone, Ronnie ; Haring, Keith ; Kiefer, Anselm ; Long, Richard ; Longobardi, Nino ; Mapplethorpe, Robert ; Merz, Mario ; Oberhuber, Oswald ; etc.
Terrae Motus, Fondazione Amelio - Istituto per l'Arte Contemporanea, Villa Campolieto - Ercolano, 6 luglio - 31 dicembre 1984
boek